MINAT MAHASISWA TERHADAP HASIL JADI BLUS DENGAN MENGGUNAKAN VARIASI TUCKING - Nahdia Rahmah, Syifa; Ridwan Misbahudin, Agus (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
The purpose of this study is to discuss the results of blouses using various tucking techniques and to determine the influence of student interest on the results of blouses using various tucking techniques. The blouses are made from dark blue denim. In this study, a quantitative approach was employed, utilising data collection techniques that included experimental methods, documentation, and the distribution of questionnaires to 64 students in the PVKK Program, specifically the Fashion Design concentration. The results showed that 64.5% of students had a high interest in the blouses made. Regression analysis yielded a significance value of 0.000 < 0.05 and an R-Square of 0.612, indicating a significant influence between the quality of the finished blouse and student interest. Tucking techniques were found to enhance visual appeal and increase student interest in the blouse, and can be further developed in fashion design education.